Exploring the use of blockchain technology in cybersecurity and data science - Rahmat, Robaisya; Abbas, Mohd Saleh; Nordin, Mohd Norazmi; Mohd Yunus, Yusmi; Muhammad, Sufri; Ismail, Albert Feisal (IEEE, 2023)
Blockchain technology has demonstrated to be extremely efficient at processing distributed transactions in a secured manner. It consists of a wide range of applications. B. To handle smart contacts and Bitcoin cash. Blockchain systems may allow automatic data exchange and thinking about, resulting in increased effectiveness and lower costs. This is made possible by the adoption of contract technology and decentralized ledgers. Additionally, blockchain technologies can enhance integrity and security of data, enabling more precise and reliable analysis of information. Ethereum along with information science integration may make it easier to create decentralized apps, opening up novel industries and income sources. However, there are still issues with adaptability, interconnection, and complexity in the combination of blockchain technology and data science. For this type of technology to achieve all of its potential advantages, it is imperative that studies and advancements in this field persist. Blockchain applications for data science are currently being investigated. This essay examines how blockchain technology is used in cybersecurity and data science.